Modernity and Post modernistic issues in Martin Amis’s and Sherzad Hassan’s Novels - Juan Abdullah Ibrahim Al-Banna; . Pakhshan Sabir Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Martin Louis Amis (1949) , is an English novelist who has written Money (1984) and London Fields(1989). These novels show the tormented selves that are divided into imaginary and real selves. This research paper presents the human miseries in the late Twentieth Century with the sense of pessimism due to uncertainty and doubt . The writer in a realistic way clarifies the modern characters challenge the obstacles that hinder their success and search for an outlet. Sherzad Hassan (1951) is a prominent and distinguished Kurdish literary figure. He is best known as storyteller, but he has also written novels and poems. He has published four collections of short stories. In this research paper , , Hassarand My father’s Dogs and , The Fog above the Abyss are discussed and compared due to the similarities and differences concerning each novelist and lights are shed on the Kurd’s sufferings.The characters in their novels are trapped in a web of reflections and shadows trying to get rid of that state and search for self-awareness. They suffer a lot while resisting such difficult situations and they are shocked by reality. Both novelists’ characters are pessimist with no hope because of the consequences of Wars , materialism and depression that are features of modernity. The research paper is concerned with an introduction and two sections. In the first, lights are shed on these aspects through features of form, style and the narrative voice in both novelists works. The second section presents samples from both novelists texts with the critics views and psychological issues related to the characters state. Then followed by a conclusion and list of references..